[Street View in Akureyri] - Streng, Evelyn Fiedler (1975)
Photograph of a street view of Akureyri, Iceland. A street intersection sits at the bottom of the photograph, surrounded by white and grey buildings. A red building with a pitched grey roof sits on a corner to the right. A parking lot full of cars is visible in the bottom right corner of the photograph. Flag poles holding up the Icelandic flag sits along the parking lot and street in the bottom right. A green, rounded mountain is visible in the background, white buildings surrounding water at the foot of the mountain.